PspA Protects Streptococcus pneumoniae from Killing by Apolactoferrin, and Antibody to PspA Enhances Killing of Pneumococci by Apolactoferrin - Shaper, Mirza (American Society for Microbiology, 2004)
Lactoferrin is an important component of innate immunity through its sequestration of iron, bactericidal activity, and immune modulatory activity. Apolactoferrin (ALF) is the iron-depleted form of lactoferrin and is bactericidal against pneumococci and several other species of bacteria. We observed that lactoferricin (LFN), an 11-amino-acid peptide from the N terminus of lactoferrin, is bactericidal for Streptococcus pneumoniae. Strains of S. pneumoniae varied in their susceptibility to ALF. Lactoferrin is bound to the pneumococcal surface by pneumococcal surface protein A (PspA). Using mutant PspA(−) pneumococci of four different strains, we observed that PspA offers significant protection against killing by ALF. Knockout mutations in genes for two other choline-binding proteins (PspC and PcpA) did not affect killing by ALF. PspA did not have to be attached to the bacterial surface to inhibit killing, because the soluble recombinant N-terminal half of PspA could prevent killing by both ALF and LFN. An 11-amino-acid fragment of PspA was also able to reduce the killing by LFN. Antibody to PspA enhanced killing by lactoferrin. These findings suggested that the binding of ALF to PspA probably blocks the active site(s) of ALF that is responsible for killing.